Examining executive function and its relationship with language outcome in children with and without cochlear implants: a behavioural and functional near-infrared spectroscopy study - Lawrence, Rachael (2022)
While cochlear implants allow many infants to develop appropriate language skills, the ability of individual children to understand speech varies widely. Established evidence suggests that neurocognitive processes contribute to variable language outcome in paediatric cochlear implant (CI) recipients. The cross-sectional and longitudinal experiments reported in this thesis aimed to investigate the association between executive function (EF) and language performance in normal-hearing (NH) and deaf-implanted children, in addition to the ability of behavioural-EF evoked brain activation and correlates of fronto-temporal cortical connectivity to predict future EF and language outcome.